Confronting failures of justice: getting away with murder and rape - Robinson, Paul H. (Rowman & Littlefield, 2024)
"No comparable volume collects in one place the various rules, doctrines, policies, and ideological positions that prevent our criminal justice system from pursuing and achieving justice"--